Transcatheter tricuspid valve repair and replacement: a landscape review of current techniques and devices for the treatment of tricuspid valve regurgitation. (4th May 2021) - Rahgozar, Kusha; Ho, Edwin; Goldberg, Ythan; Chau, Mei; Latib, Azeem
ABSTRACT: Background and Objective Tricuspid regurgitation is a prevalent and undertreated cardiac pathology impacting millions across the globe. While historically surgical interventions for isolated tricuspid regurgitation were largely avoided due to data citing poor surgical outcomes, advances in transcatheter techniques and imaging modalities have reframed the approach to tricuspid valve disease in promising new ways. Methods Here we sought to provide a landscape review of the current state of the field for transcatheter tricuspid valve interventions. We first start with a descriptive overview of the tricuspid valve, reviewing the anatomy, imaging characteristics, and the current guidelines for tricuspid interventions. We then review both transcatheter valve repair and valve replacement modalities, highlighting the devices, techniques, and valves currently under investigation, summarizing available outcomes data for each modality when possible. Results and Conclusion Our aim in writing this landscape review is the create an all-encompassing, up-to-date resource for clinicians to refer to when seeking to learn about the current state of transcatheter tricuspid valve interventions. We also hope to highlight the exciting promise of transcatheter tricuspid valve replacement in appropriate patients, and review the valves currently under development for use in the tricuspid position.